Cardiovascular effects of weight loss in old adults with overweight/obesity according to change in skeletal muscle mass - Xiaojie Cai; Menghui Liu; Xingfeng Xu; Shaozhao Zhang; Rihua Huang; Peng Wang; Lixiang He; Zhuohui Chen; Zishan Liu; Yi Zhou; Yue Guo; Xiaodong Zhuang; et al. (Wiley, 2024)
Abstract Background Patients with overweight/obesity and type 2 diabetes are encouraged to lose weight, but not all losing weight gain better cardiovascular health, especially old adults. The change in skeletal muscle mass (SMM) could be the key that explains the heterogenous cardiovascular effects of weight loss. This study aims to assess whether the cardiovascular effects of weight loss vary for those gaining skeletal muscle along with weight loss. Methods The old adults with overweight/obesity and type 2 diabetes in the Look AHEAD study having muscle measurement from dual‐energy X‐ray absorptiometry were included. Based on the weight change (WC) and SMM change (SMMC) between baseline and the 4‐year follow‐up, participants were allocated into three groups-weight gain (WG) group, weight loss with muscle loss (WL‐ML) group and weight loss with muscle gain (WL‐MG) group. Cox proportional hazards regression was performed to evaluate the cardiovascular risk of those gaining or losing SMM with weight loss compared with those gaining weight. Among the participants with weight loss, the ratio of SMMC/WC was calculated, and the association of SMMC/WC with primary cardiovascular outcome was assessed. Results A total of 491 participants were included in the study with an average age of 64.56 ± 3.81 years old. A total of 47.0% were male and 49.9% were from the intensive lifestyle intervention arm. Based on their WC and SMMC, 43 were assigned to the WG group, 373 to the WL‐ML group and 75 to the WL‐MG group. Over a follow‐up of almost 10 years, 97 participants encountered the primary endpoint. The WG group had the highest incidence of 25.59%, the WL‐MG group had the lowest incidence of 9.33% and the WL‐ML group had 21.18% (P = 0.040). In the fourth adjusted Cox model, the WL‐MG group achieved significantly decreased odds of the primary endpoint compared with the WG group (hazard ratio [HR] 0.33, 95% confidence interval [CI] [0.12, 0.87], P = 0.026), whilst the WL‐ML group did not (HR 0.91, 95% CI [0.47, 1.78], P = 0.670). Among the participants with weight loss, when SMMC/WC reached around 50%, this HR soared to approximately two‐fold. Conclusions The participants gaining SMM along with weight loss achieved the lowest odds of adverse cardiovascular events, whilst those who lost SMM along with weight loss had comparable cardiovascular risk with those gaining weight. The more muscle lost during weight loss, the greater the harm. The cardiovascular effects of weight loss were modulated by whether the participants gained SMM meanwhile losing weight.